2022
DOI: 10.7150/thno.74125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early invisible acute ischemic stroke in non-contrast computed tomography using two-stage deep-learning model

Abstract: Rationale: Although non-contrast computed tomography (NCCT) is the recommended examination for the suspected acute ischemic stroke (AIS), it cannot detect significant changes in the early infarction. We aimed to develop a deep-learning model to identify early invisible AIS in NCCT and evaluate its diagnostic performance and capacity for assisting radiologists in decision making. Methods: In this multi-center, multi-manufacturer retrospective study, 1136 patients with suspected AIS but invisible lesions in NCCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…25 The study suggested that the detection system involving two-stage DCNNs could significantly improve radiologists' sensitivity in detecting AIS, similar to a study by Lu et al, who found that using NCCT features in two-stage DCNNs to identify AIS shows high diagnostic value with AUC of 83.61%, sensitivity = 68.99%, specificity = 98.22%, and accuracy = 89.87%. 31 Our results are consistent with previous studies that used two-stage DCNNs models for lung nodule detection 33 and breast cancer classification. 34 The result showed high accuracy and competitiveness compared to existing traditional methods.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…25 The study suggested that the detection system involving two-stage DCNNs could significantly improve radiologists' sensitivity in detecting AIS, similar to a study by Lu et al, who found that using NCCT features in two-stage DCNNs to identify AIS shows high diagnostic value with AUC of 83.61%, sensitivity = 68.99%, specificity = 98.22%, and accuracy = 89.87%. 31 Our results are consistent with previous studies that used two-stage DCNNs models for lung nodule detection 33 and breast cancer classification. 34 The result showed high accuracy and competitiveness compared to existing traditional methods.…”
supporting
confidence: 92%
“… 25 The study suggested that the detection system involving two-stage DCNNs could significantly improve radiologists’ sensitivity in detecting AIS, similar to a study by Lu et al, who found that using NCCT features in two-stage DCNNs to identify AIS shows high diagnostic value with AUC of 83.61%, sensitivity = 68.99%, specificity = 98.22%, and accuracy = 89.87%. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of subtle findings that can otherwise be missed by physicians encompasses the most promising aspects of AI (Nishio et al, 2020;Kaothanthong et al, 2022;Lu et al, 2022). To aid in the detection of "invisible" acute IS, Lu and colleagues developed a deeplearning model comprised of two deep CNNs.…”
Section: Detection Of Acute Ischemic Strokementioning
confidence: 99%
“…The detection of subtle findings that can otherwise be missed by physicians encompasses the most promising aspects of AI (Nishio et al, 2020;Kaothanthong et al, 2022;Lu et al, 2022). To aid in the detection of "invisible" acute IS, Lu and colleagues developed a deeplearning model comprised of two deep CNNs.…”
Section: Detection Of Acute Ischemic Strokementioning
confidence: 99%